Analisis preferensi masyarakat terhadap minat membeli produk makanan berlabel halal di Kota Kuala Tungkal Kabupaten Tanjung Jabung Barat - Andre Prianto; Amri Amir; Paulina Lubis (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
The main objectives of this research are to analyze the characteristics of Mini Market consumers, traditional markets, and street vendors and analyze the factors that influence the interest of buying halal labeled food products in Kuala Tungkal Tanjung Jabung Barat District. The data used in this study is the primary data. The result of the research found the characteristics of the interest of the Mini Market consumers, traditional markets, and street vendors products in Kuala Tungkal Tanjung Jabung Barat District based on female gender is 64%, Islamic religion 72%, senior high school education 68%, 44% self-employed, Rp 1.000.000–Rp 2.000.000 as much as 38% and consumer response does not care about the halal label as much as 28%. the result of research indicates that comprehension, packaging, and hygiene variables influence the interest in buying halal labeled food products in Kuala Tungkal. Keywords: Halal, Consumer, Market.